New Public management and hospital professions - Belorgey, Nicolas (Saúde e Sociedade, 2018)
The New Public Management (NPM) can be defined as a set of practices and ideas with the aim of importing work methods from the private sector to the public sector. In this context, what happens to the public officials responsible for implementing public policies, those whose daily practices are directly affected by this desire for transformation? To answer this question, we use observations, interviews and questionnaires carried out as part of a thesis on French hospitals in the 2000s. We show that there is differentiation within the health professions. The NPM faces opposition of the dominant segments, whereas the dominated segments are more compromised with it, especially because they have fewer means to resist it.